Hotel for dogs - Duncan, Lois, 1934- (New York : Scholastic, 2008)
Liz and her brother wind up with nine stray dogs that need homes but must be kept a secret.
Originally published in 1971 by Houghton Mifflin.
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction